2013
DOI: 10.1097/ftd.0b013e31828d221f
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine and Norquetiapine Serum Concentrations and Clinical Effects in Depressed Patients Under Augmentation Therapy With Quetiapine

Abstract: Due to marked variability of Q and NQ concentrations in the blood, therapeutic drug monitoring may be helpful to identify pharmacokinetic peculiarities. The lack of correlation between serum concentrations of NQ and clinical improvement casts doubts on the concept that NQ is the pharmacologically active principle for the augmentation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A study in Denmark by Hasselstrøm & Linnet 24 also used TDM data for 62 patients and revealed a median Cps/DD ratio of 0.41 nmol/L/mg (0.16 ng/ml/mg) for quetiapine (all IR). Ostad Haji et al 32 reported the mean Cps/DD ratio of quetiapine (43 IR) as 0.34 ± 0.24 ng/ml/mg in 105 depressive patients by the mean DD of 222 ± 125 mg.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Denmark by Hasselstrøm & Linnet 24 also used TDM data for 62 patients and revealed a median Cps/DD ratio of 0.41 nmol/L/mg (0.16 ng/ml/mg) for quetiapine (all IR). Ostad Haji et al 32 reported the mean Cps/DD ratio of quetiapine (43 IR) as 0.34 ± 0.24 ng/ml/mg in 105 depressive patients by the mean DD of 222 ± 125 mg.…”
Section: Discussionmentioning
confidence: 99%
“…Both were assessed in patients autopsied in the study of Vignali et al The authors found (peripheral) blood levels of norquetiapine to be 258.93 (95% CI = −22.63–540.48). Blood levels of 7-hydroxy quetiapine were 45.88 (95% CI = −8.24–83.52) [ 22 , 45 ].…”
Section: Relevant Matricesmentioning
confidence: 99%
“…Non-toxic levels in postmortem blood extend to around 0.8 mg/kg, but, at the same time, toxic levels in postmortem blood can begin at 0.35 mg/kg. The serum or plasma of quetiapine overdose survivors had concentrations ranging from 1 to 10 mg/L [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%